Hemimegalencephaly and Hirschsprung's disease: a unique association - TÜRKDOĞAN, DİLŞAD (My University, 1998)
A 2-year-old boy with hemimegalencephaly and Hirschsprung's disease is reported. The unique association of these two entities is considered to be the presence of a common insult or insults that affect the innervation of the bowel and the formation of the cerebral cortex. Short-segment subtype of Hirschsprung's disease may suggest that this effect occurred between the eighth and twelfth weeks of gestation. Although there is a well-known coexistence of Hirschsprung's disease with the malformations that share a common neurocristopathic origin (abnormalities of neural crest cell growth, migration, or differentiation), a few extremely rare cases, as in this case, might reflect the coexistence of Hirschsprung's disease with a cerebral malformation (i.e., hemimegalencephaly) that is a nonneurocristopathic entity by itself.
Keywords: Humans; Male; Child, Preschool; Brain; Abnormalities, Multiple; Hirschsprung Disease; Nervous System Malformations; Spasms, Infantile